Private equity challenge - leveraged buyout of Krones - returns analysis - Iller, Filipe Luca (2023)
This document assesses the leveraged buyout (LBO) of Krones AG, a publicly traded beverage equipment manufacturer and service provider, serving as a supplementary resource to the investment committee paper (ICP). Utilizing publicly available information from sources like Bloomberg, Capital IQ, and Refinitiv, both quantitative and qualitative analyses were conducted. These include a comprehensive valuation of Krones AG, LBO modelling, and analyzing the competition landscape. Based on our analysis, the potential return on investment for the Krones AG LBO, spanning 5 years, could reach up to 3.5x the initial investment, contingent upon financial model assumptions and the success of value-creation strategies.